Mapping the distribution of the Eurasian Hoopoe Upupa epops and the Pine Processionary Moth in Lebanon based on a Citizen Science approach (Avocetta, 2023)
The Pine Processionary Moth (PPM) Thaumetopoea wilkinsoni has long been attacking Mediterranean forests. In its management strategy, Lebanon has focused mainly on pesticides, leaving natural predators as an understudied control option. This study aims to understand the distribution of the Eurasian Hoopoe Upupa epops, by assessing the damage caused by the PPM. We attempted to explain the distribution of the two species, their relation to other factors and, with a Citizen Science (CS) approach, we developed their distribution maps. We found that the varying PPM damage between cadastral units was linked to Important Bird Areas (IBAs), highlighting the importance of multiple birds, including the Eurasian Hoopoe, as natural predators of this pest and calling for their conservation. As understudied species in Lebanon, this paper sets the path and offers guidelines for future researchers willing to work on similar crucial research in a climate change context and reveal the underlying relation between the two species.